Transcription factor CTCF and mammalian genome organization - Kotova, E.S.; Akopov, S.B.; Sverdlov, E.D.; Nikolaev, L.G. (Вiopolymers and Cell, 2014)
The CTCF transcription factor is thought to be one of the main participants in various gene regulatory networks including transcription activation and repression, formation of independently functioning chromatin domains, regulation of imprinting etc. Sequencing of human and other genomes opened up a possibility to ascertain the genomic distribution of CTCF binding sites and to identify CTCF-dependent cis-regulatory elements, including insulators. In the review, we summarized recent data on CTCF functioning within a framework of the chromatin loop domain hypothesis of large-scale regulation of the genome activity. Its fundamental properties allow CTCF to serve as a transcription factor, an insulator protein and a dispersed genome-wide demarcation tool able to recruit various factors that emerge in response to diverse external and internal signals, and thus to exert its signal-specific function(s). Фактор транскрипції CTCF вважають одним з основних учасни- ків різних мереж регуляції генів, з-поміж яких активація і репресія транскрипції, утворення незалежно функціонуючих доменів хроматину, регуляція імпринтингу тощо. Секвенування геномів людини та інших организмів дозволяє виявляти геномний розподіл сайтів зв’язування CTCF та ідентифікувати CTCF-залежні регуляторні елементи, до яких належать інсулятори. В огляді підсумовано нові дані з функціонування CTCF у рамках гіпотези участі петельних доменів хроматину у великомасштабній регуляції активності геному. Фундаментальні властивості CTCF дозволяють йому діяти як регулятор транскрипції, інсуляторний білок, а також як розподілений по геному прикордонний елемент,здатний залучати різні фактори, які з’являються у відповідь на різноманітні зовнішні та внутрішні чинники і таким чином виконувати свої сигнал-специфічні функції. Фактор транскрипции CTCF считается одним из основных участников различных сетей регуляции генов, включая активацию и репрессию транскрипции, образование независимо функционирующих доменов хроматина, регуляцию импринтинга и т. д. Секвенирование геномов человека и других организмов позволяет выявить геномное рапределение сайтов связывания CTCF и идентифицировать CTCF-зависимые регуляторные элементы, включая инсуляторы. В обзоре суммированы новые данные по функционированию CTCF в рамках гипотезы участия петельных доменов хроматина в крупномасштабной регуляции активности генома. Фундаментальные свойства CTCF позволяют ему действовать как регулятор транскрипции, инсуляторный белок, а также как распределенный по геному пограничный элемент, способный привлекать различные факторы, появляющиеся в ответ на разнообразные внешние и внутренние воздействия и таким образом осуществлять свои сигнал-специфичные функции.